The role of local government in clean water management in tangerang regency a study of local regulation no. 67 of 2022 - Khaeru Tamimi; Sulkiah Hendrawati; Wahyudi Wahyudi (Institute Of computer Science (IOCS), 2024)
Clean water is a basic need that requires guaranteed provision, access, and sustainability of services for the community. Tangerang Regency Regent Regulation (Perbup) Number 67 of 2022 concerning the Community-Based Clean Water Provision Program provides the legal basis for local government intervention in clean water provision at the village/sub-district level. This study aims to analyze the role of local governments—including policy formulation, financing, technical facilitation, community empowerment, and monitoring mechanisms—in the implementation of this program. The method used is a qualitative approach through analysis of policy documents (Perbup No. 67/2022), interviews with local stakeholders, and field studies at several pilot sites. The results indicate that local governments play a central role as policymakers and financial and technical facilitators. Perbup 67/2022 clarifies the collaboration scheme between the district government, sub-district/village officials, and the community in community-based clean water provision. However, real obstacles include budget limitations, technical capacity at the village level, suboptimal inter-institutional coordination, and challenges to the operational sustainability of water facilities. Based on the findings, the main recommendations are to strengthen institutional capacity and coordination mechanisms, allocate sustainable budgets, deepen the role of PDAMs and community self-management, and establish a transparent monitoring and evaluation system to ensure equitable and sustainable access to clean water. In conclusion, Perbup No. 67/2022 offers a legal framework.